THE RELATIONSHIP BETWEEN THE SITIHINGGIL OF THE PALACES IN CIREBON WITH MAJAPAHIT ARCHITECTURE BASED ON SHAPE AND SPATIAL TRANSFORMATION - Rahadhian Prajudi Herwindo (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
There is an important old element in Kasepuhan and Kanoman Palaces called Sitihinggil. The Sitihinggil complex refers to Majapahit relics located deep in East Java. This research aims to recognize Majapahit architectural patterns in Sitihinggil Keraton in Cirebon, so it is expected that architectural relationships from the Pre-Islamic-Majapahit to the Islamic period will be identified, especially in residential buildings. The research method is carried out through a typological comparison between relics of Majapahit buildings and Sitihinggil in their architectural transformation. The study has been conducted by examining the shape transformation and the spatial pattern of the mass-spatial arrangement, figure, and ornamentation through the real form of reconstruction results and the relief picture of the Majapahit temple. This study shows a strong architectural relationship between the Sitihinggil in Kasepuhan and the architectural patterns of Majapahit era. At the same time, the Kanoman palace has changed more dynamically. Both show an architectural transformation, but Majapahit traces can still be recognized by persistent patterns such as mass patterns, figures, ornaments, and gates. This phenomenon illustrates the spirit of preservation of the past, even though the religious orientation has changed.